2021
DOI: 10.1021/acs.jpclett.1c03468
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Second-Order Møller–Plesset Theory: A More Accurate Alternative to Conventional MP2 for Noncovalent Interactions and Transition Metal Thermochemistry for the Same Computational Cost

Abstract: Second order Møller-Plesset theory provides a remarkably simple form for the electron correlation energy with many desirable properties, e.g. it is size-consistent, free of self-interaction error, and scales with the fifth power of system size. However, MP2 exhibits well-known shortcomings including an incomplete description of dispersion interactions and sizable failures for transition metal chemistry. Herein, we first explore multiple physically justified forms of single-parameter regularization and then dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(131 citation statements)
references
References 102 publications
5
111
0
Order By: Relevance
“…However, it can be certainly refined for specific applications. 106 To further evidence this, Fig. 4 reports the difference between regularized (computed at η = 1.0 E h with the SRGbased regularizer) and non-regularized quasiparticle energies as functions of R H−H for each orbital.…”
Section: Cc3mentioning
confidence: 88%
See 1 more Smart Citation
“…However, it can be certainly refined for specific applications. 106 To further evidence this, Fig. 4 reports the difference between regularized (computed at η = 1.0 E h with the SRGbased regularizer) and non-regularized quasiparticle energies as functions of R H−H for each orbital.…”
Section: Cc3mentioning
confidence: 88%
“…Other choices are legitimate like the regularizers considered by Head-Gordon and coworkers within orbitaloptimized second-order Møller-Plesset theory, which have the specificity of being energy-dependent. 77,106 In this context, the real version of the simple energy-independent regularizer (21) has been shown to damage thermochemistry performance and was abandoned. 107,108 Our investigations have shown that the following energy-dependent regularizer…”
Section: Introducing Regularized Gw Methodsmentioning
confidence: 99%
“…With the κ regularization and orbital-optimization we only find a small improvement 0.12 kcal/mol in the MAE, as expected for closed-shell systems with large HOMO-LUMO gaps. 48,126 The MAE is reduced to 0. and a dispersion correction contribution to recover the proper long-range dispersion also significantly reduces the error of DHDFs (vide supra). However, the MAE for ACONF12 with MP2D is still 0.21 kcal/mol higher than for HF-D4 due to residual basis set incompleteness and superposition errors.…”
Section: Assessment Of Dft and Wft Methodsmentioning
confidence: 99%
“…These calculations were performed using the Q-Chem 5.4 electronic structure package [99]. A value of κ = 1.1 was used for the κ-OOMP2 method, as recommended for transition metal complexes [100]. The geometry for each molecule corresponded to the B3LYP high-spin (S=5/2) optimized geometry.…”
Section: Data Availabilitymentioning
confidence: 99%